Human Resource Management Practices in Strengthening Organizational Performance through Innovation Capabilities among SME Employees - Erbin Chandra; Reina A Hadikusumo; Elly Romy; Acai Sudirman (Annals of Management and Organization Research, 2026)
Purpose: This study examines how Human Resource Management (HRM) practices, organizational agility, and technology capabilities relate to organizational performance through the mediating role of innovation capabilities among Small and Medium Enterprises (SME) employees. Methodology: This study was oriented towards quantitative research. The research sample comprised 250 SME employees. Data were analyzed using Structural Equation Modelling (SEM). Results: The findings indicate that HRM practices, organizational agility, and technological capabilities are positively associated with innovation capabilities. Innovation capability plays a significant mediating role in linking organizational resources to organizational performance. Conclusions: The findings indicate that HRM practices, organizational agility, and technological capabilities are positively associated with innovation capabilities. Innovation capabilities play a significant mediating role in linking organizational resources to organizational performance. Limitations: The cross-sectional design limits causal inference, and reliance on self-reported data may introduce a common method bias. The sample was limited to SMEs within a specific national context. Contributions: This study integrates HRM, agility, and technological perspectives within a dynamic capability framework, offering empirical evidence on capability-based performance mechanisms in SMEs and providing practical insights for SME managers.